EFFECT OF GIVING WATER EXTRACT OF SUGAR APPLE LEAF IN DRINKING WATER ON THE PHYSICAL COMPOSITION OF COCKEREL CARCASSES - D. P., Barus; Nuriyasa, I M.; Witariadi, N. M. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to determine the effect of giving water extract of sugar apple leaf through drinking water on the physical composition of cockerel carcasses. This study was conducted for 8 weeks in a farmer's cage in Dajan Peken Village, Tabanan, Bali. The study used a completely randomized design, with 5 treatments and 4 replicates. Each replicate used 3 cockerel so that a total of 60 cockerel. The five treatments were the level of sugar apple leaf extract through drinking water, namely 0%, 1%, 2%, 3% and 4% for treatment E0, E1, E2, E3 and E4 respectively. The observed variables included slaughter weight, carcass weight, carcass percentage and percentage of meat, bone and subcutaneous fat including skin. The results showed that the provision of 2 - 3% water extract of sugar apple leaf through drinking water significantly (P<0,05) increase the slaughter weight, but not significantly (P>0,05) different on carcass weight, carcass percentage, percentage of meat, bone and subcutaneous fat including skin of cockerel. Based on the results of the study, it can be concluded that the administration of 2 - 3% water extract of sugar apple leaf through drinking water can increase slaughter weight but no effect on carcass weight, carcass percentage and percentage of meat, bone and subcutaneous fat including skin of cockerel.